Sondajele de opinie și alegerile - Dorel Abraham; Sebastian Lăzăroiu (Sociologie Românească, 2001)
2000 election year in Romania freed passions and debates on public opinion polls never seen before. As political actors are getting more and more professional by incorporating social studies in their making decision process, the consequences of polls became crucial within a competitive environment with winners and losers. On the one hand the natural "illiteracy" of politicians or journalist in sampling and interviewing bring about some public misinterpretation of polls' results. On the other hand, the sociologists or pollsters spent little time introducing lay people with basic principles of their work or formulating simple rules of reading polls' results. Moreover, less effort has been invested during the last ten years into dedicated studies to measure or prove the effects of public opinion polls on voting behavior in Romania. Some people simply take into account Western professional findings on this issue. This article is trying to pay more attention to common mistakes in reading polls and also to study the effects of polls reporting on voting behavior - both changing preferences and mobilization to vote. Some conclusions on the famous bandwagon or underdog effects in Romania might really strike the one who found about them from the Western scientific literature.